Validation/Ratification of the COVID-19 post-pandemic teaching process in higher education through the usage of the SEEQ survey. - Triana Arias Abelaira (2022)
The COVID-19 pandemic has changed the teaching-learning process at all different levels of education, as well as it has changed people's lives around the world. Introduction: We have carried out this research with students of Information and Security, a subject taught in two university degrees at Extremadura University. For that purpose, we have used and analysed the data collected from the academic year 2012-13 to the current year 2021-22. Purposes: By using the validated SEEQ survey, our goal will be to prove whether there has been a significant change in the teaching-learning process since the COVID-19 pandemic in higher education, in particular in the field of Computer and Telematics Engineering. Methodology: A statistical analysis of the results of the SEEQ survey was carried out employing the SPSS programme. For this, all the data collected have been divided into two large groups, one called pre-pandemic (with the data related to the year 2019-20) and the other one called post-pandemic (with the data corresponding to the two subsequent years). Results: The statistical analysis of the data requires the usage of non-parametric tests since the conditions of normality are not met in the Kolmogorov-Smirnov and Shapiro-Wilks tests. Consequently, we have applied the Mann-Whitney U methodology, wherein in all cases, the result obtained retains the null hypothesis, which indicates that the changes are not significant.  Conclusions: The general conclusion of this research is that, if the average of all categories of the SEEQ survey continues to increase, this change is not statistically significant. It is also very important to underline that the mean of all categories is above the mean on the Likert scale; in fact, the vast majority are around 4 points out of 5, which is a very positive result.